A fully automatic group selection for form-finding process of truncated tetrahedral tensegrity structures via a double-loop genetic algorithm - Lee, Seunghye; Gan, Buntara Sthenly; Lee, Jaehong (Composites. Part B, Engineering, 2016)
Numerous studies have developed novel form-finding methods of tensegrity structures using various techniques. Previous works have been limited by the lack of a fully automatic grouping technique in the form-finding process. In this study, an advanced form-finding method of tensegrity structures using a fully automatic labeling that can specify the member types. Constraint optimization problems were then used in the form-finding processes to minimize fitness functions by using a double-loop genetic algorithm. A well-known truncated tetrahedral tensegrity is presented to demonstrate the accuracy and efficiency of the proposed method. In conclusion, a very good performance of presented method has been shown in the results. •An advanced method for form-finding of tensegrity structures is presented.•A fully automatic group selection can be obtained using a penalty strategy with discrete strut condition.•A double-loop GA is used to effectively guide the searching direction towards promising solutions.•The constraint minimization problems by using the equilibrium equations are used.•A very good performance of presented method has been shown in the results.